Feasibility of a concept out-of-autoclave carbon fibre reinforced polymer part manufacturing process. (5th September 2019) - Taylor, Tom; Yanagimoto, Jun
Feasibility of a concept out-of-autoclave carbon fibre reinforced (thermoset) polymer (CFRP) part manufacturing process, in which hot forming and curing of prepreg are integrated in one step, was demonstrated. Optimal forming-temperature, dwell-temperature and/or dwell-time with respect to formability, springback and mechanical properties of the formed part were determined for two representative laminate thicknesses of 0.3 and 0.5 mm by V-bend part forming followed by macroscopic observation, Scanning Electron Microscopy and flexural testing of formed parts. Benchmarking against parts manufactured by the traditional autoclave-process demonstrated feasibility of the concept process for manufacturing high-quality parts, principally for lightweight structural automotive engineering applications. Compared to Resin Transfer Moulding, considered the industry benchmark Out-of-Autoclave process, opportunity for reduced manufacturing time to within 300 s per part and through a much more simple process for reduced lead-time, reduced financial cost and greater environmental sustainability, was highlighted.